Evaluation of Intra-Articular Amikacin Administration in an Equine Non-inflammatory Joint Model to Identify Effective Bactericidal Concentrations While Minimizing Cytotoxicity - Pezzanite, Lynn; Chow, Lyndah; Hendrickson, Dean; Gustafson, Daniel L.; Russell Moore, A; Stoneback, Jason; Griffenhagen, Gregg M.; Piquini, Gabriella; Phillips, Jennifer; Lunghofer, Paul; Dow, Steven; Goodrich, Laurie R. (Frontiers in Veterinary Science, 2021)
Septic arthritis causes significant morbidity and mortality in veterinary and human clinical practice and is increasingly complicated by multidrug-resistant infections. Intra-articular (IA) antibiotic administration achieves high local drug concentrations but is considered off-label usage and appropriate doses have not been defined. Using an equine joint model, we investigated effects of amikacin injected at three different doses (500, 125, 31.25 mg) on immune and cartilage responses in tibiotarsal joints. Synovial fluid (SF) was sampled at multiple time points over 24 hours, cell counts determined, and amikacin concentrations measured by liquid chromatography mass spectrometry. Cytokine concentrations and collagen degradation products in SF were measured by ELISA and multiplex immunoassays. Mean amikacin concentrations in SF were ≥MIC (0.004 mg/ml) for most common equine joint pathogens at all time points tested to 24 hours for all three amikacin doses evaluated. Inflammatory cytokines tumor necrosis factor-alpha (TNF-α) and interleukin-1 (IL-1β) increased significantly in SF in the highest amikacin dose group, despite the fact that increases in SF cell counts were not observed. Similarly, biomarkers of cartilage type II collagen cleavage (C2C, C12C) were increased in SF following amikacin injection. Mechanistically, we further demonstrated using in vitro studies that chondrocytes and synoviocytes killed by exposure to amikacin underwent apoptotic cell death and were phagocytosed by macrophages in a non-inflammatory process resembling efferocytosis. Neutrophils and T-cells were susceptible to amikacin cytotoxicity at clinically relevant doses, which may result in blunting of cellular inflammatory responses in SF and account for the lack of increase in total nucleated cell counts following amikacin injection. In summary, decisions on whether to inject cytotoxic antibiotics such as aminoglycosides intra-articularly and what doses to use should take into account the potential harm that antibiotics may cause and consider lower doses than those previously reported in equine practice.